Institutional integrated teletandem: students' perceptions about collaborative writing - Cavalari, Suzi Marques Spatti (2016)
Institutional integrated teletandem (iiTTD) is characterized “as a series of teletandem sessions that are embedded in regular FL lessons (thus mandatory) so that such lessons both feed and are fed by teletandem practice” (CAVALARI; ARANHA, [2016]). Collaborative writing is conceived as an activity in which learners work together throughout the process of planning, generating ideas, structuring, editing and revising a text in the foreign language (STORCH, 2013). This paper aims at (i) describing a collaborative writing task that was implemented within iiTTD at UNESP – São José do Rio Preto, and (ii) discussing Brazilian learners’ perceptions as they carried out such task in 2015. Data were collected by means of learning diaries written by thirteen students of English as a foreign language who were taking a Translation Studies major.